The maid and the crocodile ebook - Ifueko, Jordan (Raybearer., 2024)
A romantic standalone fantasy set in the world of Raybearer , from New York Times bestselling author Jordan Ifueko The smallest spark can bind two hearts . . . or start a revolution. In the magic-soaked capital city of Oluwan, Small Sade needs a job—preferably as a maid, with employers who don't mind her unique appearance and unlucky foot. But before she can be hired, she accidentally binds herself to a powerful being known only as the Crocodile, a god rumored to devour pretty girls. Small Sade entrances the Crocodile with her secret: she is a Curse Eater, gifted with the ability to alter people's fates by cleaning their houses. The handsome god warns that their fates are bound, but Small Sade evades him, launching herself into a new career as the Curse Eater of a swanky inn. She is determined to impress the wealthy inhabitants and earn her place in Oluwan City . . . assuming her secret-filled past—and the revolutionary ambitions of the Crocodile God—don't catch up with her. But maybe there is more to Small Sade. And maybe everyone in Oluwan City deserves more, too, from the maids all the way to the Anointed Ones.